Sengketa Ombudsman dan Pelayanan Publik: Perlindungan Hak-Hak Warga Negara : Penelitian - Sikstus Dominikus L B Jawang; Dhoni Martien; Ismail (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The Ombudsman is a concrete commitment to the principles of good governance, increasing transparency, accountability, and building publik trust in the government. The Ombudsman acts as a mediator and supervisor, as well as being an independent institution dedicated to resolving disputes under the Ombudsman's own interests, when disputes arise from the implementation of publik services that are deemed detrimental and impact access to justice for citizens' rights to obtain adequate publik services without any arbitrary action. The aim of this research is to find out how important the role of the Ombudsman is in publik service disputes in order to protect the rights of citizens in obtaining publik services as is the aim of the concept.Good Governance.The method of this research uses the normative legal research method. The Ombudsman as an independent institution as an effort to achieveGood Governancein encouraging effective and efficient state and government administration, honest, open, clean, and free from corruption, collusion, and nepotism, maintaining clean publik services, good publik services, efficient and professional administration of justice without any bias towards other agencies and providing quality services for citizens as a form of granting the rights that citizens should receive in obtaining justice, a sense of security, and prosperity.